ANALISIS KEPUASAN PELAYANAN ANTENATAL CARE DI PUSKESMAS KABUPATEN BULELENG PADA MASA PANDEMI COVID-19 - Kurniasari, Ni Made Dian; Utami, Ni Komang Sri Marisa (ARCHIVE OF COMMUNITY HEALTH, 2024)
During the COVID-19 pandemic situation, many restrictions and changes were made to almost all routine health services including Maternal and Child Health (MCH) services. Changes to the ANC system at the Buleleng 1 Health Center have never been evaluated, this is very important to do to determine the satisfaction of pregnant women as a measure of the success of service delivery. This research is a quantitative study with a cross-sectional approach which aims to analyze the level of satisfaction and the factors that influence satisfaction with ANC services at the Buleleng 1 Health Center during the COVID-19 pandemic which were analyzed using the Logistic Regression Test. This research was conducted at the Buleleng 1 Health Center in December 2022 - January 2023 with 82 samples. The results obtained were that most of the pregnant women who came were aged 20-35 years, had higher education, did not work, had low incomes, used BPJS PBI and mothers with their first pregnancies. As many as 60.98% of mothers were satisfied with the services provided, but the other 17% were dissatisfied. The main complaints of pregnant women are the cleanliness of the toilets, the provision of a place to wash hands and hand sanitizers, long waiting times, convoluted service procedures, and the use of PPE by officers who are not good. Puskesmas need to make efforts to optimize facilities and infrastructure, waiting times, service procedures as well as the use of PPE for officers during the pandemic to improve the quality of service. Keywords: antenatal care, patient satisfaction, pandemic, regressi logistic